Motor proficiency in normal children and with learning difficulty: a comparative and correlational study based on the motor proficiency test of Bruininks-Oseretsky - Nilson Roberto Moreira; Vitor da Fonseca; Alves Diniz (Revista da Educação Física)
The aim of this investigation is to verify the difference between children with learning disabilities and children without learning disabilities through motor proficiency test of Bruininks and Ozeretsky (1978). The sample was constituted by 30 children, with 8-year average age, 15 males and 15 females, subdivided into two groups of 15 children from both sexes: children without learning disabilities attending 3rd grade and children with learning disabilities attending 2nd grade having failed a term once. All of them came from a middle class background, according to Grafar scale (adapted by Fonseca, 1991). All children presenting any other disabilities were excluded from the sample. Intelligence factor “G” was controlled by using a percentile, higher or equal to 50 (middle and high level), measured by Raven’s (1974) progressive combinations test. In motor proficiency, children with learning disabilities showed significant differences when compared with normal children of the same age, in all components of global, composed and fine motricity. The tests administered showed a strong correlation between the variables of the motor proficiency components. The results lead to the conclusion that there were significant differences in motor proficiency between normal children and children with learning disabilities, who showed specific motor difficulties evincing a more vulnerable motor profile and not the presence of neurological dysfunction signs.